Different effects of p53 protein overexpression on the survival of gastric cancer patients according to Lauren histologic classification: a retrospective study - Kim, Ki Wook; Kim, Nayoung; Choi, Yonghoon; Kim, Won Seok; Yoon, Hyuk; Shin, Cheol Min; Park, Young Soo; Lee, Dong Ho; Park, Young Suk; Ahn, Sang-Hoon; Park, Do Joong; Kim, Hyung-Ho; et al. (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2021)
Background Inactivation of TP53 , a tumor suppressor gene, is associated with the development of several malignancies, including gastric cancer (GC). The present study aimed to evaluate the correlation between the overexpression of p53 and survival in different Lauren-type GCs. Methods From May 2003 to December 2019, 3608 GC patients treated endoscopically or surgically at the Seoul National University Bundang Hospital were enrolled for the study. Immunohistochemical staining for p53 was performed on all endoscopic and surgical gastric specimens. Clinicopathologic characteristics with Lauren classification, survival rate, and cancer recurrence were analyzed according to p53 overexpression. Results Among 3608 GC patients, p53 overexpression was seen in 1334 patients (37%). p53 overexpression was associated with lower depth of invasion ( P = 0.026) and Early gastric cancer ( P = 0.044) in intestinal-type GC, and with advanced TNM stage ( P < 0.001) and Advanced gastric cancer ( P < 0.001) in diffuse-type GC. The overall survival (OS) and GC-specific survival (GCSS) were significantly lower in p53 overexpression positive patients. This significance was more pronounced and enhanced in the diffuse-type GC and was absent in the intestinal-type GC. In multivariate analyses, p53 overexpression was associated with poor OS in both subtypes of GC and cancer recurrence in diffuse-type GC. (OS in intestinal-type: adjusted hazard ratio [aHR] = 1.423, P = 0.022; OS in diffuse-type: aHR = 1.401 P = 0.035; cancer recurrence in diffuse-type: aHR = 1.502, P = 0.039). Conclusion p53 overexpression was associated with poor prognosis in GC, especially in diffuse-type. In addition, p53 overexpression was associated with early stage disease in intestinal-type GC and with advanced stage disease in diffuse-type GC.